(untitled) (INNOVATIVE ECONOMY, 2026)
Dziubanovska N.V. FORMATION OF REGIONAL LOGISTICS SYSTEMS OF THE WESTERN MACRO-REGION OF UKRAINE UNDER THE CONDITIONS OF ECONOMIC RECOVERY AND SUSTAINABLE DEVELOPMENT Purpose. The aim of the article is to examine the specific features of the formation of regional logistics systems in the western macro-region of Ukraine under conditions of economic recovery and sustainable development. Methodology of research. The research is based on a set of general scientific and special methods, including statistical analysis, comparison, dynamic analysis, structural analysis, and generalization. The analysis of the dynamics of road freight turnover, the assessment of regional shares in the national indicator, and the method of spatial and functional interpretation of logistics systems were applied to substantiate the conclusions. Findings. The dynamics of road freight turnover of Lviv, Ivano-Frankivsk, and Ternopil regions for 2014–2025 were analysed. The uneven nature of logistics processes development was identified, and three stages were distinguished: stabilization, growth, and adjustment. A wave-like dynamic of the share of the studied regions in the road freight turnover of Ukraine was revealed, with a peak in 2022 and a subsequent decline in 2024–2025. A spatial and functional model of the regional logistics system of the western macro-region was substantiated. Originality. The approach to studying regional logistics systems based on the integration of quantitative and spatial analysis has been further developed, which made it possible to substantiate a spatial-functional model of the logistics system of Ukraine’s western macro-region and determine the role of individual regions within its structure. Practical value. The obtained results may be used to substantiate directions for the development of regional logistics systems, improve transport and logistics infrastructure, and foster interregional logistics linkages in the context of Ukraine’s economic recovery. Key words: logistics system, regional logistics, road freight turnover, western macro-region, logistics links, transport infrastructure, economic recovery, sustainable development.